Stress-Induced Changes in Nucleus Accumbens Glutamate Synaptic Plasticity - Campioni, Matthew R; Xu, Ming; McGehee, Daniel S (Journal of neurophysiology, 2009)
1 Committee on Neurobiology and 2 Department of Anesthesia and Critical Care, University of Chicago, Chicago, Illinois Submitted 3 October 2008; accepted in final form 2 April 2009 Stress hormones released in the CNS following exposure to unavoidable, aversive stimuli have been shown to alter the physiology of neurons in multiple brain regions including hippocampus, amygdala, prefrontal cortex, and ventral tegmental area. The nucleus accumbens (NAc), a motor-limbic interface linked to motivation and reward, receives inputs from each of these stress-affected brain regions, raising the possibility that its function might also be altered in response to stress. To assess potential stress-induced plasticity in the NAc, we exposed adult mice to daily cold water forced swim for 2 consecutive days and conducted electrophysiological experiments assessing glutamate receptor function in brain slices taken 18–24 h following the second swim. We found that AMPA receptor (AMPAR)/ N -methyl- D -aspartate receptor (NMDAR) ratios, a measure of synaptic strength, were increased in the NAc shell but not core medium spiny neurons (MSNs) in stressed animals relative to controls. This effect was blocked by preadministration of glucocorticoid receptor (GR) antagonist RU486, suggesting that the observed changes are dependent on corticosteroid signaling. The role of corticosterone (CORT) in the observed plasticity was confirmed, because exogenous administration of 10 mg/kg CORT also enhanced AMPAR/NMDAR ratios in the NAc shell. The synaptic changes in NAc shell MSNs reflect an enhancement of AMPAR-mediated currents, as we observed increased AMPAR miniature postsynaptic current (mEPSC) amplitude following stress but no change in NMDAR mEPSCs. We hypothesize that altered information processing via plasticity of excitatory inputs might contribute to reward-related behaviors such as stress-induced reinstatement of drug seeking in animals and relapse in humans. Address for reprint requests and other correspondence: D. S. McGehee, Univ. of Chicago, Dept. of Anesthesia and Critical Care, 5841 S. Maryland Ave., Chicago, IL 60637 (E-mail: dmcgeheeatuchicago.edu )